The reconstruction of historical national accounts: the case of Italy - Fenoaltea, Stefano (PSL Quarterly Review, 2010)
This paper reviews the evolution of Italy’s historical national accounts. The Italian accounts were among the very first to be compiled; they have also been more thoroughly critiqued and revised than perhaps any other, and the process has yet to reach closure. This paper considers the Italian real product series for the period between Unification and World War I. After briefly reviewing the available sources and the evolution of the estimates themselves, it moves on to methodological issues; and these are of general import, for Italy’s historical accounts were initially compiled with the standard methodology that also informed, and largely continues to inform, their counterparts for other countries. The revision of the Italian accounts highlights the pitfalls of that methodology, and, correspondingly, the weakness of the extant world-wide corpus of historical national accounts. JEL Codes: C82, N01, N13